A Coloured South African Teacher in Aotearoa New Zealand - Stanley, Eleanore Caroline (Auckland University of Technology, 2022)
This dissertation investigates my personal identity and how it has been shaped by large historical and social forces, including racism, colonialism and patriarchy. I am an immigrant South African teacher in Aotearoa New Zealand: one of many who appreciate living in a society where overt racism is not accepted. Being Coloured meant I knew both worlds and could accept what each brought: languages, cultures and value systems. I had an advantage over many relatives and friends since I had developed my sense of identity early in life, and was equally proud of all sides of my family heritage. Migration is a conscious decision to leave one’s country of birth and re-establish oneself in another country. People migrate for a variety of reasons – new opportunities, for a safer environment for their families, for a better life. Acceptance by the adoptive country determines how well the migrant can settle into life there. I found that the concept of ‘Coloured’ was often viewed as unacceptable in Aotearoa New Zealand. I realised the need to be open about my bi-ethnic heritage, which led to my acceptance. Having been brought up as a native speaker of English and with knowledge of British culture worked to my advantage as a teacher in Aotearoa New Zealand. A clear sense of identity and pride in my ethnic heritage has given me tolerance for cultural difference that is an advantage in developing a culturally responsive classroom practice.
Keywords: Autoethnography; Identity; Coloured South African; Racism; Teacher; Aotearoa New Zealand